Online repression and transnational social movements: Thailand and the #MilkTeaAlliance - Joakim Kreutz; Anthi Antonia Makrogianni (Political Research Exchange)
Research on the formation of transnational social movements primarily view these as either exile support of a local movement or mobilization around an international issue. This article presents a different argument for transnational activism drawing on the logic of the repression-dissent nexus when considering the combination of online and offline performances of contemporary social movements. The starting point is that membership in online communities constitutes a social identity for potential protest participants that can be activated and politicized when states’ seek to repress access and content to online interaction. Since online communities are borderless by nature, we suggest that when regimes employ online repression due to local protests then we will see a backlash that will facilitate the formation of a transnational social movement. We illustrate our argument with an empirical discussion about how the anti-government protests in Thailand in 2020 became part of and facilitated a growing transnational social movement of youth discontent with regimes in Southeast and East Asia. The example shows that the impetus for increasing transnational co-operation throughout the process was in response to growing repression by the Thai authorities both of online content and on the street.